2013
DOI: 10.1007/s10803-013-1894-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Parenting Behavior and Child Behavior Problems in Families of Children and Adolescents with Autism Spectrum Disorder

Abstract: Parents of a child with autism spectrum disorder (ASD) face specific challenges in parenting, but concrete parenting behavior has never been properly investigated in these families. This exploratory questionnaire study compared parenting behaviors among mothers of children and adolescents with ASD (n = 552) and without ASD (n = 437) and examined associations between child behavior problems and parenting behavior. Results showed that mothers of children with ASD reported significantly lower scores on Rules and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
54
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 59 publications
(64 reference statements)
11
54
1
5
Order By: Relevance
“…These findings replicated an observational study, indicating that mothers of adolescents with ASD exhibit more sensitivity while handling a conflict, compared to mothers of TD adolescents (van Esch et al, ]. Our findings also correspond with reports of mothers to children with and without ASD [Maljaars et al, ]. According to these reports, significant changes occur in the transition from childhood to adolescence: whereas mothers of typically developing children show a significant reduction in the use of positive parenting strategies, mothers of adolescents with ASD continue to exhibit positive parenting during adolescence, as they have done throughout childhood.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings replicated an observational study, indicating that mothers of adolescents with ASD exhibit more sensitivity while handling a conflict, compared to mothers of TD adolescents (van Esch et al, ]. Our findings also correspond with reports of mothers to children with and without ASD [Maljaars et al, ]. According to these reports, significant changes occur in the transition from childhood to adolescence: whereas mothers of typically developing children show a significant reduction in the use of positive parenting strategies, mothers of adolescents with ASD continue to exhibit positive parenting during adolescence, as they have done throughout childhood.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that parent–child reciprocity in preschoolers with ASD, which was lower than that of their TD peers [Hirschler‐Guttenberg et al, ], still predicted higher social skills in childhood [Haven, Manangan, Sparrow, & Wilson, ]. In addition, compared to mothers of TD children, mothers of children with ASD scored higher on a questionnaire examining positive parenting, including scales measuring positive involvement and problem solving [Maljaars et al, ]. During adolescence, these positive findings remained stable among mothers to adolescents with ASD, while the scores of mothers of TD children declined as the child grew‐up [Maljaars et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher levels of positive parenting behaviors have been associated with lower levels of child externalizing behavior problems in typically developing children (Boeldt et al 2012; Maljaars et al 2014), and there is some research to indicate similar patterns among children with ASD. Internalizing and externalizing problems in children with ASD have been associated with several parental and family factors, important considerations given that individual child characteristics often account for only a small amount of variance in psychopathology (Gadow et al 2008; Mayes et al 2011; Sukhodolsky et al 2008).…”
Section: Introductionmentioning
confidence: 99%